Kant on mental illness, emotions and moral responsibility - Ferrara, Ilaria (Con-Textos Kantianos. International Journal of Philosophy, 2021)
The paper discusses some thematic issues that emerge from the Kantian study of diseases of cognition and volition, taking into consideration his anthropological works and some problems emerging from his main critical works. Starting from the explanation of the taxonomy of the main mental illnesses (and their causes), some epistemological themes will be illustrated, linked to the fallible relationship between transcendental truths and the empirical dimension of knowledge and to the Kantian concept of error. Subsequently, the study of affects and passions, conceived as illnesses of volition, will show the difficulties linked to a total involvement of reason in moral action, concerning the shortcomings of human action with respect to the principle of responsibility. Finally, the paper will focus on the role of legal imputability in relation to moral responsibility and to mental diseases.